Efficiency of Using NPK Fertilizer with Vermicompost Addition to Growth and Results of Soybean Plants - M. Arifin; P. Sukaryorini; T. Mujoko (Nusantara Science and Technology Proceedings)
The continued use of chemical fertilizers and pesticides on agricultural land, causing damage to land which results in degradation of land productivity. Organic agriculture is a green revolution movement that reduces agricultural inputs in the form of the use of organic fertilizers and pesticides, by using local natural resources in a sustainable manner. This study aims to determine the use of vermicompost and chemical fertilizers on the growth and yield of soybean plants. This study used a randomized block design (RBD) with vermicompost (V) and NPK (NPK) treatment, the treatment of which was: (P0) 750.0 kg ha-1 NPK, (P1) 562.5 kg ha-1 NPK + 30 ton ha-1 V, (P2) 375.0 kg ha-1 NPK + 30 tons ha-1 V, (P3) 187.5 kg ha-1 NPK + 30 tons ha-1 V and (P4) without chemical fertilizer + 30 tons of tonnes ha-1 V. Each treatment combination is repeated 3 times, so 15 experimental units are obtained. The results showed that administration of 30 tons ha-1 gave unreal results with other treatments for the growth and yield of Glycine max.